2018
DOI: 10.1128/aem.01616-18
|View full text |Cite
|
Sign up to set email alerts
|

Stress Resistance Development and Genome-Wide Transcriptional Response of Escherichia coli O157:H7 Adapted to Sublethal Thymol, Carvacrol, and trans -Cinnamaldehyde

Abstract: Thymol, carvacrol, and -cinnamaldehyde are essential oil (EO) compounds with broad-spectrum antimicrobial activities against foodborne pathogens, including O157:H7. However, little is known regarding direct resistance and cross-resistance development in O157:H7 after adaptation to sublethal levels of these compounds, and information is scarce on microbial adaptive responses at a molecular level. The present study demonstrated that O157:H7 was able to grow in the presence of sublethal thymol (1/2T), carvacrol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 61 publications
(68 reference statements)
4
21
0
1
Order By: Relevance
“…Similarly, BssS was reported to reduce bacterial biofilm formation by influencing cell signaling, and the deletion of the bssS gene was found to increase biofilm formation in E. coli (29). Consistent with these observations, our previous RNA sequencing study (14) revealed that multiple points of biofilm formation pathways were affected, including genes for the biosynthesis of flagella (flhCD, fliAZ, and flgM), poly-N-acetylglucosamine (csrB), colonic acid (wza), and curli (csgD).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Similarly, BssS was reported to reduce bacterial biofilm formation by influencing cell signaling, and the deletion of the bssS gene was found to increase biofilm formation in E. coli (29). Consistent with these observations, our previous RNA sequencing study (14) revealed that multiple points of biofilm formation pathways were affected, including genes for the biosynthesis of flagella (flhCD, fliAZ, and flgM), poly-N-acetylglucosamine (csrB), colonic acid (wza), and curli (csgD).…”
Section: Resultssupporting
confidence: 82%
“…Our previous study (14) using RNA sequencing revealed altered expression of various virulence genes in E. coli O157:H7 grown to early stationary phase in the presence of sublethal Thy, Car, or TC, including genes related to flagellar biosynthesis and function, chemotaxis, biofilm development, type III secretion systems (T3SS), and efflux pumps. However, the biological significance of these transcriptional changes has not yet been verified.…”
mentioning
confidence: 99%
“…It was hypothesised that induced uptake of iron would enhance microbial survival under stress conditions and contribute to microbial oxidative resistance (by sequestering free irons, which generate ROS). This study also reported decreased expression of genes associated with motility and biofilm formation [226]. We have also observed downregulation of flagella Biofilm formation in the cinnamaldehyde exposed strain increased when grown on a plastic surface (Table 5.2).…”
Section: Cinnamaldehydesupporting
confidence: 72%
“…A study by Yuan et al [226] showed that exposure to cinnamaldehyde caused an upregulation in genes associated with metabolism but virulence genes associated with biofilm formation were repressed in E.coli. This could explain the decrease in biofilm formation after exposure to cinnamaldehyde.…”
Section: Formation Of Bacterial Biofilms Grown On Urinary Catheters Amentioning
confidence: 99%
See 1 more Smart Citation